Influence of Health Education on Prevention of Drug Abuse - LO Chukwuka; F Agoreyo (Journal of Applied Sciences and Environmental Management)
The increasing scourge of drug abuse among adolescents is a major challenge facing mankind. As the importance of health education in disease prevention is enormous, drug misuse prevention programme requires introducing innovations, flexibility and reinforcement which will be effective in shortest possible time among the greatest number of people. This study was undertaken to investigate the influence of health education on prevention of drug abuse. 192 adolescents comprising of male and females, randomly selected from two secondary schools and a university were used as sample with ages ranging from 12-22years with a mean of 17years. The questionnaire, “DA Behaviour Inventory” was administered on the sample. Data was collected and analyzed using the t-test statistics at 0.05 level of significant difference. The findings showed that there is no significant difference in the pattern of drug abuse between adolescents with knowledge of drug education and those without knowledge of drug education. There is no significant difference in the pattern of drug abuse between male and female adolescents, there is no significant difference between the pattern of drug abuse of adolescents from upper and lower socio-economic background. Also there is no significant difference in the pattern of drug abuse of early and late adolescents. These findings were discussed and the implications as well. Recommendations and suggestions for further research were given.